Musicians' medicine - potential health problems among violinists and violists caused by playing the string instrument - the review of the literature - Gabriela Ręka; Piotr Machowiec; Marcela Maksymowicz; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2021)
Introduction and purpose             Musicians' medicine has received increasing attention recently. It is known that listening to music or playing an instrument has beneficial effects on cognitive and neural functions. Playing the string instrument demands repetitive precise movements of fingers and arms in a non-ergonomic posture that might give rise to health problems. The study aims to present the current state of knowledge regarding different potential health problems among violinists and violists. The article reviews the 24 newest scientific publications available on PubMed and Google Scholar. A brief description of the state of knowledge             The literature review indicated several potential health consequences of excessive playing the violin or viola, as follows: Fiddler's neck and skin allergy, Garrod's pads, temporomandibular disorders, carpal tunnel syndrome, cubital tunnel syndrome, tennis elbow, compression of the right ulnar nerve in the ulnar (Guyon's) canal, rotator cuff tendonitis, tenosynovitis, bursitis, focal dystonia, thoracic outlet syndrome, bone asymmetry, pain in the neck, cheeks, fingers, wrist, forearm, shoulder, waist, and the back. Conclusions             Musicians should be aware of potential health problems that occur during prolonged playing the violin or the viola. An important issue is maintaining the accurate proportions between the amount of time spent playing the instrument and resting. The first signs of neurological or musculoskeletal changes should prompt the musician to seek professional medical help to prevent the disorder's progression.